Sudan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper explains that in Sudan, the public information campaign should be launched as early as possible following a decision to phase out subsidies. This campaign should comprise wide-ranging consultations with all stakeholders, and should inform the public about the high costs and unequal distribution of the subsidy benefits. Cash transfers could be used to mitigate the impact of fuel subsidy removal on the lowest income groups. In the case of the removal of subsidies on fuel products, it is estimated that the cost of compensating the lowest income groups could be achieved at a cost of less than 1 percent of GDP a year. Two decades of economic sanctions led to the exit of most Correspondent Banking Relationships (CBRs) from Sudan, and weighed heavily on trade, investment, growth, and humanitarian relief. In 2017, the United States revoked trade and financial sanctions, while sanctions imposed by the UN, and other countries, including the EU, remain applicable.